2019
DOI: 10.1097/jat.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Implementing a Mobility Technician in the General Medicine and Surgical Population to Increase Patient Mobility and Improve Hospital Quality Measures: A Pilot Study

Abstract: Background: Hospital-associated disability (HAD) has been linked to prolonged and inappropriate immobility. HAD and increased postacute care (PAC) rehabilitation spending are also associated. Purpose: This pilot aims to describe the implementation processes of a designated mobility technician (MT), providing daily mobility on a medical and surgical acute care unit. During the MT implementation, we explore the resulting effects on patient length of stay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…In line with previous studies, the majority of patients showed a change in mobility score when healthcare professionals used the JH-HLM to assess mobilization of hospitalized patients [ 12 , 17 , 21 , 30 ]. However, our findings also show that when healthcare professionals used the AMEXO scale to assess early postoperative mobilization instead, the number of patients who show a change in mobility score during the first three postoperative days was significantly higher.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In line with previous studies, the majority of patients showed a change in mobility score when healthcare professionals used the JH-HLM to assess mobilization of hospitalized patients [ 12 , 17 , 21 , 30 ]. However, our findings also show that when healthcare professionals used the AMEXO scale to assess early postoperative mobilization instead, the number of patients who show a change in mobility score during the first three postoperative days was significantly higher.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies did not report a ceiling effect when healthcare professionals use the JH-HLM scale to assess mobilization in adult patients admitted to general medicine, neuroscience or general surgical ward [ 11 – 13 , 17 , 20 , 21 , 30 ]. The ceiling effect found in this study might be explained by the fact that ceiling effects are often encountered when an existing scale is applied to a new target population [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these outcomes reached statistical significance. Yet, definite conclusions cannot be drawn due to small sample size, short pilot duration, and limited data on demographics of the baseline data group ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Economic factors were investigated in one study, concluding that a mobility technician could be cost-effective by helping reduce length of stay and discharge to post-acute rehabilitation facilities. However, these outcomes were not significantly altered ( 25 ). Two trials created new roles for implementing the intervention ( 16 , 25 ), which could increase costs, while the others used pre-existing staff ( 18 20 , 24 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 98%